2008
DOI: 10.1111/j.1467-6443.2008.00331.x
|View full text |Cite
|
Sign up to set email alerts
|

Rules, Red Tape, and Paperwork: The Archeology of State Control over Migrants

Abstract: Conventional accounts of a drastic shift to migration restriction after World War I following a golden era of free movement obscure crucial processes of state formation around matters of administering migration. How and with what consequences did state control over migration become acceptable and possible after the Great War? Existing studies have centered on core countries of immigration and thus underestimate the degree to which legitimate state capacities have developed in a political field spanning sending… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(10 citation statements)
references
References 44 publications
1
6
0
1
Order By: Relevance
“…One of the five findings of the analysis (Hypothesis 1) was that the ease of hiring foreign labor influences the degree to which highly-skilled personnel, such as self-initiated expatriates, are attracted to a business environment. This finding supports research that indicates that the ease of obtaining work and residency permits in a timely manner is a major concern for self-initiated expatriates (Mäkelä and Suutari, 2013; Martin, 2008; Mahroum, 2000). The ease of obtaining work permits and employment for accompanying partners may also be an important concern (Permits Foundation, 2009, Mäkelä and Suutari, 2013).…”
Section: Findings and Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…One of the five findings of the analysis (Hypothesis 1) was that the ease of hiring foreign labor influences the degree to which highly-skilled personnel, such as self-initiated expatriates, are attracted to a business environment. This finding supports research that indicates that the ease of obtaining work and residency permits in a timely manner is a major concern for self-initiated expatriates (Mäkelä and Suutari, 2013; Martin, 2008; Mahroum, 2000). The ease of obtaining work permits and employment for accompanying partners may also be an important concern (Permits Foundation, 2009, Mäkelä and Suutari, 2013).…”
Section: Findings and Discussionsupporting
confidence: 89%
“…Prior studies have found that the policies and laws of a nation play a major role in determining how attractive it is to skilled professionals and self-initiated expatriates (Dickmann and Cerdin, 2014; Martin, 2008; Mahroum, 2000). They cite the regulation of employment, discriminatory and anti-discriminatory laws, light regulation and political stability as major concerns influencing the decisions of skilled professionals and self-initiated expatriates to relocate across national boundaries (Dickmann and Cerdin, 2014).…”
Section: Origins and Development Of Hypothesesmentioning
confidence: 99%
See 1 more Smart Citation
“…Formal temporary foreign worker programs became more common as states developed the capacity to regulate migration, which was not a given but an accomplishment (Cook-Martín, 2008; McKeown, 2008). The United States pioneered a first bracero program between 1917 and 1922, initially to meet war-induced labor shortages.…”
Section: Temporary Migration Regimes: Past and Presentmentioning
confidence: 99%
“…Desde una perspectiva comparada, ciertos trabajos han mostrado las singularidades que manifestaron las políticas migratorias en el país durante este momento histórico a partir de su contraste con la experiencia de otros Estados receptores como en los casos de Brasil, Estados Unidos, Canadá y Australia (Sánchez Alonso 2004 o Francia (Devoto 2004). Por otro lado, desde el campo de la sociología histórica, se han realizado diversos aportes originales al explorar la producción de diferencias de género al interior de las políticas migratorias mediante un análisis del sistema migratorio constituido por Italia, España y Argentina (Cook-Martín 2006), así como el modo en que el control migratorio fue admitido de manera generalizada como un dominio administrativo legítimo a partir de los mecanismos creados en respuesta a los desafíos suscitados por la "inmigración masiva" entre mediados del siglo XIX y la década de 1930(Cook-Martín 2008. El interés por la formación histórica de los controles migratorios y la construcción social y política de la "ilegalidad" también derivó en algunos análisis sobre la producción estatal de la figura del "migrante ilegal" (Domenech 2011) y las prácticas de expulsión de extranjeros en la Argentina (Domenech 2015).…”
Section: Introductionunclassified